Autonomy support, controlled coaching styles and skills development in water polo - Mladenovic, M.; Trunic, N.; Djurovic, M.; Vucic, D. (Facta Universitatis: Series Physical Education and Sport, 2015)
Self-determination theory suggests that a coach`s behavior can be viewed in terms of two interpesonal styles: autonomy supportive and controlling. This study was carried out in order to reveal possible connection between coaching styles and improvement in water polo sports practice. During three months period, two experimental groups of young male athletes practicing water polo (each N=10), age ranged 5 to 12, were under special coaching treatment (autonomy supportive or controlled). Autonomy supportive style exibits taking the athletes perspective and providing explanatory rationales when prescribing action, provide much choice as possible in the situation. Controlled coaching style means assigning tasks and activities without the input of the subordinates, showing little interest in how athletes see things, and assuming mantle of infallibility and imperviousness to questioning. Before, and at the end of experimental period, athletes from both groups were measured for speed swimming, and have been graded for performing on two water polo techniques. Age of each participant and experience in water polo practice were taken into account. M, SD, t-test, Anova and correlation analysis were applied. Statistical analysis revealed that both groups of young athletes made statistically significant improvement, although there is no statistical significance between groups. It can be said that sports trainging itself, made improvement of performance in given tests. But, there are some indications that acquisition of speed performance is more suited with controlled coaching style, while autonomy supportivness is providing better climate for developing water polo techniques.